The international organization of credit states and global finance in the world-economy - Germain, Randall D. 1961- (Cambridge studies in international relations, 1997)
In this book, Randall Germain explores the international organization of credit in a changing world economy. At the centre of his analysis is the construction of successive international organisations of credit, built around principal financial centres (PFCs) and constituted by overlapping networks of credit institutions, mainly investment, commercial, and central banks. A critical historical approach to international political economy (IPE) allows Germain to stress both the multiple roles of finance within the world economy, and the centrality of financial practices and networks for the construction of monetary order. He argues that the private global credit system which replaced Bretton Woods is anchored unevenly across the world's three principal financial centres: New York, London, and Tokyo. This balance of power is irrevocably fragmented with respect to relations between states, and highly ambiguous in terms of how power is exercised between public authorities and private financial institutions